MENGENAL LEBIH DEKAT DENGAN PENYAKIT BUSUK PANGKAL DAN ATAS KELAPA SAWIT (BASAL DAN UPPER STEM ROT) - Lisnawati; Wismaroh Sanniwati Saragih; Ahmad Rafiqi Tantawi; Hamidah Hanum; Suzanna Fitriani Sitepu; Irda Safni; Khairunnisa Lubis (LPPM UNINUS, 2024)
Basal stem rot and upper stem rot of oil palms caused by Ganoderma boninense are important oil palm diseases faced by oil palm plantations in Indonesia. For many years, basal stem rot was found to infect older oil palms that were more than 25 to 30 years old, but the disease began to appear in oil palms that were 10 to 15 years old and was even found infecting oil palm nurseries. Community service will be carried out in October 2023 in Gunung Ambat village, Sei Bingai District, Langkat Regency. The aim of this service is for the public to receive information about prevention and actions that will be taken by smallholder oil palm plantation farmers in the Sei Bingai sub-district, Langkat Regency. The expected target is for the community to distinguish attacks caused by G. boninense so that prevention can be carried out early and there is no decline in people's palm oil production. The community service method is carried out through lectures, discussions, and direct visits to people's oil palm plantations. The implementation of service activities was carried out in preparation by coordinating with community leaders and extension workers, as well as the implementation unit of the Sei Bingai sub-district agricultural service, Langkat Regency. Carrying out lectures and discussions with a team of lecturers and students targeting smallholder oil palm plantation farmers.